1998
DOI: 10.1097/00005176-199802000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pancreatic Enzymes on Zinc Absorption in Cystic Fibrosis

Abstract: These results indicate that fractional absorption of zinc is impaired by pancreatic insufficiency in patients with cystic fibrosis, and is improved by exocrine pancreatic enzyme replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…The mean fractional absorption was approximately half that for normal infants fed a cow milkbased, iron-fortified formula (0.22 Ϯ 0.04) (20). We have observed significant improvement in fractional zinc absorption with pancreatic enzyme replacement in older children (21). Such an effect was not evident in these infants for either feeding type, but the apparent lack of benefit may be related to the small number of infants on enzymes and to the finding that Figure 1.…”
Section: Discussionmentioning
confidence: 70%
“…The mean fractional absorption was approximately half that for normal infants fed a cow milkbased, iron-fortified formula (0.22 Ϯ 0.04) (20). We have observed significant improvement in fractional zinc absorption with pancreatic enzyme replacement in older children (21). Such an effect was not evident in these infants for either feeding type, but the apparent lack of benefit may be related to the small number of infants on enzymes and to the finding that Figure 1.…”
Section: Discussionmentioning
confidence: 70%
“…In this population it is reflected by their higher H Z-score and serum cholesterol values. The group of Hambidge showed a decreased fractional absorption of Zn in PI CF and its increase by pancreatic enzyme supplementation (2). The faecal Zn loss correlated with faecal fat loss (32).…”
Section: Discussionmentioning
confidence: 95%
“…Since in our healthy controls (1) 12.6 % has a serum Zn concentration below the lower cut-off of the NHANES II study (3), they could be considered as a population at risk for Zn deficiency. Therefore it is interesting to have a closer look at populations with diseases known to cause increased Zn losses such as CF (2,32). Especially since the data on prevalence of Zn deficiency in the CF population are inconsistent (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope studies have demonstrated lower absorption in infants and adolescents, especially without enzyme replacement therapy [53], and fecal excretion of endogenous zinc was observed in infants to significantly correlate with fecal fat excretion [54]. For infants and children <2 years of age who are not growing despite apparently adequate nutritional intake, a 6-month trial of zinc supplementation (1 mg zinc/kg/day) has been recommended [55].…”
Section: Acquired Zinc Deficiencymentioning
confidence: 99%